Cross-Cultural Narration in the Nineteenth Century: Jewish Folk Narratives Transcribed by a Polish AuthorMedkulturna pripoved v 19. stoletju: Judovske ljudske zgodbe, ki jih je zapisal poljski avtor - Bar-Itzhak, Haya (Studia mythologica Slavica, 2007)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The authoress discusses “The Miracle in the Cemetery” (“Cud na kirkucie”) by the Polish author Klemens Junosza and uses it to examine an important topic related to folk literature and the circumstances of its narration. Considered are the basic theoretical issues in the study of folk literature, specially cross-cultural narration and its influence on the text created in such a situation.